SURVEI KETERSEDIAAN SARANA DAN PRASARANA PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN PADA SEKOLAH MENENGAH PERTAMA NEGERI SE-KECAMATAN KUBU TAHUN 2021 (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The availability of sports and health physical education facilities and infrastructure in State Junior High Schools throughout Kubu District in 2021 is quite ideal. The purpose of the study to be achieved is to determine the state of physical education learning facilities and infrastructure for sports and health in state junior high schools throughout Kubu sub-district. This type of research is descriptive qualitative, because it aims to describe the availability of sports and health physical education facilities and infrastructure through the existing amount with the need for learning. The population in this study was two public junior high schools in Kubu sub-district and the sample in this study was physical education teachers with data collection through observation, documentation and checklists from the list of availability of sports and health facilities and infrastructure. Data analysis uses data reduction, data display, and conclusion drawing. The results of this study are known that the sports and health facilities and infrastructure owned by 2 State Junior High Schools in Kubu sub-district are SMP Negeri 1 Kubu with a result of 42.81% (quite ideal) and SMP Negeri 2 Kubu with a result of 42.19% (quite ideal), it can be concluded that the end of state junior high schools in Kubu sub-district in 2021 with a total of 42.5% in the category is quite ideal. For the facilities and infrastructure of the School Health Business (UKS), the two State Junior High Schools in Kubu sub-district are categorized as very good.Key Word: Availability, facilities and infrastructure, physical education and health